Nutritive value of Quercus pyrenaica Willd browse species in NE of Portugal - Castro, Marina (2014)
Quercus pyrenaica Willd (pyrenean oak) occurs in a transition between the Mediterranean sclerophyllous and the temperate deciduous forest, being one of the most abundant and characteristic oak species in the Iberian Peninsula, due our economical and biological importance and by several services produced. The aim of this study was to assess the nutritive value of key browse species of Pyrenean oak Mediterranean Ecosystems in Trás-os-Montes region (Portugal). The study was to undertake at different mature stages the evolution of chemical composition and in vitro digestibility of shrub twigs and tree leaves. The browse species evaluated were Cytisus scoparius (L.) Link, Cytisus striatus (Hill) Rothm, Cytisus multiflorus (LHér.) Sweet, Genista falcata Brot. and Quercus pyrenaica. Tree samples were formed by foliage and shrub by mixed twigs from several specimens. Hand-samples of the different species were taken along the year seasons, in five moments of the year, begin May in late spring, July in summer, and final September in autumn, December in winter and begin March in early spring. Quercus pyrenaica was sampled only during the leaf production periods in five moments too. The dates were: May, July, August, September, and October; regarding different stages of leaves: very young leaf, young leaf, mature leaf, leaf in early of senescence, senescent leaf. Species varied widely in crude protein content (CP) (10.06-22.57 gKg-1 DM), neutral detergent fibre content (NDF) (36.03-66.53 gKg-1 DM), acid detergent fibre content (ADF) (24.22-53.50 gKg-1 DM), acid detergent lignin content (6.20-15.76 gKg-1 DM) and in vitro digestible organic matter (IVOMD) (39.21-70.39 %). Cytisus sp. showed the higher CP and IVOMD values. Shrub species showed the highest nutritive value in late spring and the lowest values in autumn. Oak leaves presented a constant composition along the leaf cycle just, this pattern changed in very young leaf stages when leaves were not formed.